Seaweed processing: Efficiency, kinetics, and quality attributes under solar drying - Khan, Nida; Sudhakar, Kumarasamy; Rizalman, Mamat (Elsevier Ltd, 2025)
Traditional open sun drying methods face issues such as weather dependence, contamination risk, inconsistent drying rates, and nutrient loss. This study investigates a novel photovoltaic (PV)-integrated solar dryer designed to improve seaweed drying efficiency by effectively removing moisture content. Addressing the needs of Malaysian seaweed growers for a reliable and efficient drying method, this research compares conventional open sun drying with solar drying by evaluating key parameters such as moisture removal rate, drying rate, and dryer efficiency. Using a sample size of 100 grams, experimental results demonstrated that moisture loss was higher with solar drying, resulting in significantly lower final weights for Sargassum polycystum (43.8 g) and Cystoseira barbata (40.1 g) compared to open sun drying (55.81 g and 52.9 g, respectively). The drying rate for seaweed in the solar dryer was also higher, with Sargassum polycystum at 7.03 g/hr and Cystoseira barbata at 7.5 g/hr, compared to 5.52 g/hr and 5.89 g/hr for open sun drying. Additionally, the drying efficiency of the solar dryer outperformed open sun drying, with Sargassum polycystum achieving 9.52 % and Cystoseira barbata 10.13 %, compared to 7.4 % and 7.9 %, respectively, for open sun drying. Economic analysis revealed an estimated annual profit of USD 2270, indicating the economic viability of the proposed system. The findings suggest that the PV-integrated solar dryer offers a promising alternative to traditional drying methods, providing enhanced efficiency and economic benefits for seaweed farmers.